Quantization of wideband speech parameters using scalar and vector quantization methods - Madrid, Karla Morales (2004)
Wideband speech coding offers significant improvements in speech quality over narrowband speech coding in any telecommunication system. At rates of 16 kbps or lower, wideband speech applications include high-quality audio and video teleconferencing, and 3rd generation mobile communications. Wideband speech covers 50 Hz to 7000 Hz of the spectrum and is sampled at 16 kHz. Various wideband speech codes have been proposed and some have been accepted for standardization. Parametric coders offer acceptable speech quality at the lowest bit rates. In this thesis, quantization is performed on the parameters produced by two wideband parametric speech models. For the wideband LP model, Multi-stage vector quantization (MSVQ) is implemented on the LP filter coefficients. Scalar quantization methods are applied to the parameters of the wideband sinusoidal model. By varying the model parameters and the bit allocations for each parameter, different configurations of the speech coders are generated. Subjective and objective testing is performed to evaluate the quality of the synthesized speech produced by the coders. The main goal is to produce a low-bit rate wideband parametric speech coder.